Improvement and computational complexity reduction in estimating the direction of arrival using switched active switched parasitic antenna arrays for next- generation networks - Jasem, Rabah (Al-Nahrain Journal for Engineering Sciences, 2026)
This research studies the capabilities of antenna arrays known as switched active switched parasitic antennas (SASPA) in enhancing the direction of arrival (DOA) estimation of received signals. In these arrays, a single antenna element operates in an active state while the other antenna elements are parasitic at one time of measurement. In the next measurement time, a parasitic element is switched to an active state while the active element is switched to a parasitic state, and the procedure is quickly repeated for each array element. By a straightforward arrangement of SASPA measurements, a functional steering matrix can be produced without any unitary transformation. This steering matrix results from a real-valued matrix that contains the information on the DOAs of the received signals, multiplied by a vector that represents the mutual coupling. The advantages of this steering matrix contribute to obtaining high-resolution DOA estimation with considerably reduced processing time compared to the conventional antenna arrays where all antenna elements are in an active state. The simulations conducted in this study evidently demonstrate that the resolution of DOA estimation with SASPA arrays is considerably superior, irrespective of the array’s compact size and the directions and proximity of received signals to each other. Additionally, other simulations in this work depict that the processing time for DOA estimation using SASPA arrays is significantly reduced (approximately one-third less on average) in comparison to traditional all-active antenna arrays.